Approximation of Hydrogen Induced Delayed Fracture of Overlaid Cladding in Pressure Vessels Steel Structure - Ronnie H. Rusli; T. Fujita (Journal of Engineering and Technological Sciences, 2008)
Distribution and electronic states of interstitial hydrogen atoms in the iron lattice are discussed in regard to their influence to the lattice bonding, and theory of hydrogen induced delayed fracture of steel based upon it is proposed. Characteristics of delayed fracture are accordingly well accounted for.